(untitled) (CIPEEX, 2022)
THE PRESENT STUDY IS A LITERATURE REVIEW WHICH AIMS TO DESCRIBE ALTERATIONS IN THE CENTRAL NERVOUS SYSTEM (CNS) ON CHILDREN BORN OF CHEMICALLY DEPENDENT MOTHERS AND, THUS, PROVIDE CONSISTENT BASES TO FUTURE DEVELOPMENT OF STRATEGIES FOR TREATMENT AND PREVENTION IN PRIMARY CARE, CONSIDERING THE SOCIAL CONTEXT OF MOTHER/FETUS BINOMIAL. MAINLY, THE EDUCATION AND HEALTH ASPECTS, SOCIOECONOMIC AND CULTURAL CONDITIONS. THE METHODOLOGY USED HAS INCLUDED THE DATA RESEARCH OF 5 ORIGINAL ARTICLES PRODUCED SINCE 2018, WHICH WAS RELATED TO THE TOPIC, FREE OF CHARGE AND FOUND IN THE DATABASES BIBLIOTECA VIRTUAL DE SAÚDE (BVS), PUBMED, SCIELO. IN SUM, THE GENERAL RESULTS HAVE DEMONSTRATED ABNORMALITIES IN THE CENTRAL NERVOUS DEVELOPMENT, FREQUENT CRYING, RESPIRATORY DISTRESS, TREMORS OF THE NEWBORNS AND SEVERAL DIFFICULTIES FOR A RESOLUTIVE TREATMENT. THE SUBJECT HAS DIFFERENT NUANCES, SINCE NEONATAL ABSTINENCE SYNDROME (ANS) DOES NOT LIMIT ITSELF TO ILLICIT DRUG USE, BUT ALSO EMBRACES ANTIDEPRESSANTS, ALCOHOL AND OTHER MEDICATIONS. SO, IT IS NECESSARY TO PAY ATTENTION TO DETERMINATE CAUSES OF MICROCEPHALY, PREMATURE BIRTH AND UNEXPECTED NEURO-MOTOR DEVELOPMENT; ALL ARE SYMPTOMS OF THAT SYNDROME. THEREFORE, THERE IS AN URGENT NEED TO DEVELOP MORE STUDIES ABOUT IT, SO THAT PRIMARY CARE OVERCOMES THE CHALLENGES OF THE SEPARATION OF THE MOTHER/FETUS BINOMIAL AND THE ADVERSITIES IN THE USE OF MEDICATIONS, WHICH ARE SIMILARS TO THE DRUGS USED BY THE PREGNANT WOMEN, IN THE REHABILITATION OF BOTH.